The Correlation between Rooming-in and the Level of Independence of Postpartum Mothers in Caring for Newborns in the Inpatient Room of RSU Bali Royal - Agustini, IGA Ratih; Prihandini, Claudia Wuri; Siwi, Ni Luh (Basic and Applied Nursing Research Journal, 2024)
Introduction: Rooming-in, or co-hospitalisation, is designed to teach postpartum mothers how to independently care for their newborns, recognise their babies' responses, and establish a strong bond. This approach is particularly crucial for mothers who exclusively breastfeed. This study aimed to determine the correlation between rooming-in and the level of independence of postpartum mothers in caring for their newborns at RSU Bali Royal, emphasising the importance of health education regarding postnatal care. Methods: This quantitative study employed an observational, analytical, and descriptive design with a cross-sectional approach. The sample comprised all postpartum mothers who gave birth at Bali Royal General Hospital and met the inclusion criteria. A total of 92 respondents were included. Data were collected using a detailed questionnaire and analysed using the Spearman Rank Test. Results: The study found that 53.3% of the respondents required assistance in caring for their newborns. The correlation value of 0.784 indicated a strong relationship between rooming-in and the level of independence of postpartum mothers. Conclusion: There is a strong correlation between rooming-in and the independence level of postpartum mothers in caring for newborns at RSU Bali Royal. Promoting rooming-in practices can significantly enhance the independence of postpartum mothers.